2019
DOI: 10.1109/tpwrs.2019.2891840
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Critical Parameters Affecting Voltage and Angular Stability Considering Load-Renewable Generation Correlations

Abstract: The renewable energy source based generating technologies and flexible demand and storage devices exhibit significant temporal and spatial uncertainties in generating and loading profiles and introduce additional level of uncertainty in network operation. The dynamic behaviours of such a network can be affected and the stable operation may be compromised. This paper proposes a probabilistic analysis approach for the evaluation of the effect of uncertain parameters on power system voltage and angular stability.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 44 publications
1
23
0
1
Order By: Relevance
“…Several research papers have reported the dynamic voltage stability issue by considering load dynamic and dynamic VAr compensation [4]- [6]. Despite there being many works (many others not mentioned for brevity) regarding voltage stability assessment and corrective measures, very few reported the post fault dynamic voltage signature.…”
Section: B Literature Reviewmentioning
confidence: 99%
“…Several research papers have reported the dynamic voltage stability issue by considering load dynamic and dynamic VAr compensation [4]- [6]. Despite there being many works (many others not mentioned for brevity) regarding voltage stability assessment and corrective measures, very few reported the post fault dynamic voltage signature.…”
Section: B Literature Reviewmentioning
confidence: 99%
“…In the modern power system, stability is only determined by the physical characteristics of SGs. Such a system increasingly relies on the complex control of renewable generation, the range of system operating conditions, and the grid code by the transmission system operators (TSOs) [3].. Several studies have reported the dynamic voltage stability characteristics by considering load dynamics and dynamic VAr compensations [4][5][6]. The primary reason for dynamic voltage instability in the system is the lack of reactive power support during the disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…LFC is an imperative area in the field of power systems. In literature, extensive work has been done for minimizing the frequency fluctuations due to load variations that lead to strained system and can potentially cause power system breakout 4 . Frequency is the core parameter which needs to be maintained for a reliable supply to the load.…”
Section: Introductionmentioning
confidence: 99%